Annotated list of amphibian and reptile taxa described by Ilya Sergeevich Darevsky (1924–2009) - Barabanov, Andrei V.; Doronin, Igor V. (Zootaxa, 2020)
Ilya S. Darevsky co-described 70 taxa (three genera, 46 species, 21 subspecies) in 44 publications belonging to five orders, eight families of amphibians and reptiles during his career in herpetology. Of this number, three taxa are fossil and 57 taxa are currently considered as valid. By the regions where new taxa were discovered Southeast Asia and Western Asia (includes Caucasus and Asia Minor) dominates. The largest number of descriptions was published in the Russian Journal of Herpetology.